PENGGUNAAN MEDIA KANTONG BILANGAN UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS 1 MADRASAH IBTIDAIYAH AL-ISLAM RINGINANOM - Miskiya, Zakiyyatul; Wafirah, Milna; Hasyim HS, Ahmad Fuad; Sholikhun, Muhamad (Universitas Mataram, 2024)
The community service activity aims to enhance the quality and motivation of mathematics learning in Grade 1 at Al-Islam Ringinanom Madrasah Ibtidaiyah, particularly focusing on addition concepts. This service was conducted on August 8-9, 2023. The object or target of this community service activity is 10 students from Grade 1 at Al-Islam Ringinanom Madrasah Ibtidaiyah in the Tempuran district. The stages involved in this community service included field observation, coordination with partners, program socialization, program implementation, and evaluation. The utilization of the number pocket media in teaching mathematics to Grade 1 students at Al-Islam Ringinanom Madrasah Ibtidaiyah has proven to have a positive impact on students' learning outcomes. Before the intervention, the classical completion percentage was 50%, whereas in Cycle II, this figure surged to 90%. These results indicate an improvement in both the grades and the classical completion rate of students after the implementation of the intervention